Near-room-temperature tunable dielectric response induced by dual phase transitions in a lead-free hybrid: (C3H8N)2SbBr5. Issue 24 (5th June 2019) - Li, Maofan; Teng, Bing; Han, Shiguo; Yang, Tao; Li, Yaobin; Liu, Yi; Zhang, Xinyuan; Liu, Xitao; Luo, Junhua; Sun, Zhihua
Abstract : We report a new lead-free organic–inorganic hybrid that undergoes the dual phase transitions near room temperature. Abstract : Organic–inorganic hybrid materials, which exhibit structural diversity and rich physical properties, have shown great potential as basic device elements in the optoelectronic field. Herein, we report a new lead-free organic–inorganic hybrid compound, [C3 H8 N]2 SbBr5 (1, where C3 H8 N + is the cyclopropylammonium cation), which demonstrates tunable dielectric responses near room temperature, derived from its two successive structural phase transitions at the vicinity of T 1 = 290 K and T 2 = 315 K, respectively. That is, its dielectric constants change from high-dielectric (above T 2 ), moderate-dielectric (between T 2 and T 1 ) and low-dielectric states (below T 1 ). Such dielectric behaviors coincide well with a series of reversible thermal peaks in the DSC curve. Further structural analyses reveal that the order–disorder of organic cationic moieties accounts for the phase transition at T 2, while the change of the molecular configuration provides the driving force to the phase transition at T 1 . Such phase transition behaviours differ from those of the majority of previously reported dielectric phase transition materials. Moreover, theoretical calculation of the electronic band structure of1 reveals the direct feature with a band-gap value of ∼2.36 eV. This work affords broader design flexibility for the future exploration of electrically-ordered materials in the organic–inorganic hybrid family.